Sulforaphane improves mitochondrial metabolism in fibroblasts from patients with fragile X-associated tremor and ataxia syndrome - Napoli, Eleonora; Flores, Amanda; Mansuri, Yasmeen; Hagerman, Randi J.; Giulivi, Cecilia (Neurobiology of disease, 2021)
CGG expansions between 55 and 200 in the 5′-untranslated region of the fragile-X mental retardation gene (FMR1) increase the risk of developing the late-onset debilitating neuromuscular disease Fragile X-Associated Tremor/Ataxia Syndrome (FXTAS). While the science behind this mutation, as a paradigm for RNA-mediated nucleotide triplet repeat expansion diseases, has progressed rapidly, no treatment has proven effective at delaying the onset or decreasing morbidity, especially at later stages of the disease. Here, we demonstrated the beneficial effect of the phytochemical sulforaphane (SFN), exerted through NRF2-dependent and independent manner, on pathways relevant to brain function, bioenergetics, unfolded protein response, proteosome, antioxidant defenses, and iron metabolism in fibroblasts from FXTAS-affected subjects at all disease stages. This study paves the way for future clinical studies with SFN in the treatment of FXTAS, substantiated by the established use of this agent in clinical trials of diseases with NRF2 dysregulation and in which age is the leading risk factor. •Sulforaphane improved mitochondrial bioenergetics in FXTAS.•Bioenergetic improvement was observed with high CGG repeats and disease stage.•Sulforaphane promoted NRF2-dependent and -independent mechanisms of action.